Coagulation Abnormalities Associated with Stroke or Porencephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The prevalence of genetic and functional coagulation abnormalities in 59 children (age 0-18 years) with arterial ischemic stroke or porencephaly was compared with previously published population frequencies in a study at the National Institute for Neurological Disorders and Stroke, Bethesda, MD.